2001
DOI: 10.1055/s-2001-12011
|View full text |Cite
|
Sign up to set email alerts
|

Artery Relaxation by Chalcones Isolated from the Roots of Angelica keiskei

Abstract: An EtOAc-soluble fraction from a 50% EtOH extract of the roots of Angelica keiskei inhibited phenylephrine-induced vasoconstriction in rat aortic rings, while an EtOAc-insoluble fraction had no effect at 100 micrograms/ml. Five active substances isolated from the EtOAc-soluble fraction of the roots were identified as xanthoangelol (1), 4-hydroxyderricin (2), and xanthoangelols B (3), E (4) and F (5), which inhibited phenylephrine-induced vasoconstriction at the concentrations of 10-100 micrograms/ml. It was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…Previously, it has been reported that A. keiskei extract produces elevation of the serum HDL level and a reduction of liver triglyceride levels in hypertensive rats. 8) Some chalcones isolated from A. keiskei inhibit phenylephrine-induced vasoconstriction in vivo 9) and regulate nuclear factor (NF)-kB activation. 10) Moreover, some chalcones isolated from it reportedly have inhibitory effects against tumor promoter activity, [11][12][13] antitumor and antimetastatic activities 14,15) Humulus lupulus (commonly known as "hop cones" or "hops") is cultivated in the temperate zones of the world.…”
Section: )mentioning
confidence: 99%
“…Previously, it has been reported that A. keiskei extract produces elevation of the serum HDL level and a reduction of liver triglyceride levels in hypertensive rats. 8) Some chalcones isolated from A. keiskei inhibit phenylephrine-induced vasoconstriction in vivo 9) and regulate nuclear factor (NF)-kB activation. 10) Moreover, some chalcones isolated from it reportedly have inhibitory effects against tumor promoter activity, [11][12][13] antitumor and antimetastatic activities 14,15) Humulus lupulus (commonly known as "hop cones" or "hops") is cultivated in the temperate zones of the world.…”
Section: )mentioning
confidence: 99%
“…Recent studies have also indicated that the extracted chalcones from the roots of Angelica keiskei KOIDZUMI have beneficial effects including vasodilatation, antitumor and antimetastatic activities. [17][18][19] The purpose of the present study is to evaluate whether chalcones extracted from Angelica keiskei KOIDZUMI have an inhibitory effect on NF-kB activation. To attain this, we examined the effects of xanthoangelol, xanthoangelol D, E, and F on NF-kB activation in PAECs.…”
Section: )mentioning
confidence: 99%
“…An equal volume of stop solution (0.04 N HCl in isopropanol) to that of the culture medium was then added to each well and the absorbance at 570 nm (peak) and 630 nm (bottom) was ; Funabashi, Japan: c Department of Materials and Applied Chemistry, College of Science and Technology, Nihon University;[1][2][3][4][5][6][7][8] Japan: and d Department of Pediatrics, School of Medicine, Nihon University; 30-1 Oyaguchikami-cho, Itabashi-ku, Tokyo 173-0032, Japan. Received February 28, 2005; accepted April 25, 2005 Xanthoangelol, a major chalcone constituent of the stem exudates of Angelica keiskei, was evaluated for cell toxicity and apoptosis-inducing activity in human neuroblastoma (IMR-32) and leukemia (Jurkat) cells.…”
Section: -[45-dimethylthiazol-2-yl]-25-diphenyltetrazolium Bromidementioning
confidence: 99%